The medicinal properties of tisane in the tradition «With days and pots we shall overcome» - Flores García, Emely Marucehí (2023)
The tisaneras, characters that take part in the tradition «Con días y ollas venceremos», by don Ricardo Palma, were those saleswomen who offered, in the morning hours, the tisanas, medicinal drinks as well known in the Viceroyalty as in the first years of the Peruvian Republic, to the point that we could say that the tisaneras are the ancestors of the emolienteros of our times. They were the heirs of traditional medicine of pre-Inca and Inca origin, and the depositaries of ancestral knowledge about the medicinal properties of plants from our immense natural heritage. During the viceregal and republican periods, tisanes were deeply rooted in Lima because they solved the health problems that afflicted the population, such as colds, muscular pains, respiratory ailments, anxiety, etc. For this reason, we consider it relevant to investigate the curative properties of this drink, which, in modern medicine, represents a great contribution to pharmacopoeia, as it is based on ancestral knowledge of the therapeutic properties of various plants.